Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/s41598-017-17596-4
|View full text |Cite
|
Sign up to set email alerts
|

Milder degenerative effects of Carfilzomib vs. Bortezomib in the Drosophila model: a link to clinical adverse events

Abstract: Proteasome inhibitors, e.g. Bortezomib (BTZ) and Carfilzomib (CFZ), have demonstrated clinical efficacy against haematological cancers. Interestingly, several adverse effects are less common, compared to BTZ, in patients treated with CFZ. As the molecular details of these observations remain not well understood we assayed the pathophysiological effects of CFZ vs. BTZ in the Drosophila experimental model. Mass Spectrometry analyses showed that neither CFZ nor BTZ are hydrolysed in flies’ tissues, while at doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…The peripheral neuropathy effects of the BTZ combination were approximately 5 fold higher than CFZ combination 13 . A very recent study, showed the mechanisms of milder cardiotoxic effects of CFZ compared to BTZ in the Drosophila model 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The peripheral neuropathy effects of the BTZ combination were approximately 5 fold higher than CFZ combination 13 . A very recent study, showed the mechanisms of milder cardiotoxic effects of CFZ compared to BTZ in the Drosophila model 14 .…”
Section: Introductionmentioning
confidence: 99%
“…As reported before, 16,17 we noted that for both JJN3 ( Figure S2C) and RPMI 8226 ( Figure S2D) cells, the Rub999, Rub1024 and PR671A inhibitors selectively suppressed the CT-L, C-L and T-L activities, respectively. Thus, as was suggested, [19][20][21] the high percentage of cell death in MM cells achieved by BTZ and EPOX (and likely CFZ) is associated with co-inhibition of more than one proteasomal peptidases. These findings also support the notion that the CT-L activity is the rate limiting for protein breakdown and accordingly, selective inhibition of the β5 peptidase by Rub999 increased cell death, yet, as mentioned less effectively and at higher concentrations as compared to BTZ or EPOX, and likely CFZ.…”
Section: Among Pis That Are Highly Selective For Specific Proteasommentioning
confidence: 75%
“…Thus, co-inhibition of either the C-L or the T-L sites is required to effectively inhibit protein breakdown and to increase sensitivity of MM cells and/or other types of cancer cells (eg solid tumours) to PIs. 16,19,20 In support, head-to-head comparison of clinically available PIs showed that in the clinically relevant setting only the co-inhibition of C-L or T-L with CT-L activity achieves meaningful functional proteasome inhibition and cytotoxicity; in this setting, the selective CT-L/T-L inhibition of both constitutive and immunoproteasome is the most cytotoxic. 21 In terms of the affected cell signalling pathways, non-lethal proteasome inhibition induced PI-, time-and cell type-specific readouts, likely due to differences in the genetic backgrounds of the cell lines under study 29 ; this heterogeneity at both the genome and transcriptome levels among tumours from different patients is a MM hallmark seen also at the clinical setting.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…UPP inhibitors which have demonstrated clinical efficacy include bortezomib (BTZ) [19] and carfilzomib [20]. BTZ is a slowly reversible inhibitor that binds the catalytic site of the 26S proteasome enabling inhibition of the CT-L and, to a lesser extent, of C-L and T-L activities [19, 21, 22]. Nevertheless, the development of severe adverse effects linked to the usage of proteasome inhibitors, such as peripheral neuropathies and/or cardiovascular diseases, along with inherent or acquired drug resistance remain a significant clinical problem [19, 23].…”
Section: Introductionmentioning
confidence: 99%